Altered distributions in circulating follicular helper and follicular regulatory T cells accountable for imbalanced cytokine production in multiple sclerosis. (25th April 2021) - Haque, R; Kim, Y; Park, K; Jang, H; Kim, S Y; Lee, H; Kim, H J
Summary: Follicular T helper (Tfh) and regulatory (Tfr) cells are distinct subsets of CD4 + T lymphocytes, regulating humoral immune responses in the germinal center. It is widely accepted that dysregulated Tfh and Tfr cells are associated with autoimmunity. In this study, we evaluated the frequencies of circulating chemokine receptor (CXCR)5 + programmed cell death 1 (PD-1 + ) Tfh (cTfh) and CXCR5 + PD-1 + forkhead box protein 3 (FoxP3 + ) CD25 + Tfr (cTfr) cells, and their corresponding cytokines from the peripheral blood mononuclear cells of 28 patients with relapsing–remitting multiple sclerosis (MS) and 16 age- and sex-matched healthy controls (HC). Subsets of cTfh cells by Th1- and Th17-related surface markers (CXCR3 and CCR6) were also evaluated. We found that the frequency of cTfh cells was significantly higher in MS patients compared to that of HC. Conversely, the frequency of cTfr cells was lower in MS patients than that of HC. Interleukin (IL)-21-producing cTfh cells were significantly increased in MS patients, while IL-10-secreting cTfr cells were lower in MS patients compared to levels in HC. Among cTfh cells, cTfh17.1 cells were the major subtypes that were significantly increased in MS patients compared to HC, with the frequency of IL-21-secreting cells being the highest. These results suggest that an imbalanced distribution of cTfh and cTfr exist in MS patients, which contributes to the reciprocally altered IL-21 and IL-10 production. Graphical Abstract: